Crystallization and diffraction analysis of β-N-acetylhexosaminidase from Aspergillus oryzae - Vaněk, Ondřej; Brynda, Jiří; Hofbauerová, Kateřina; Kukačka, Zdeněk; Pachl, Petr; Bezouška, Karel; Rezáčová, Pavlína (Acta crystallographica. Section F, Structural biology and crystallization communications, 2011)
Fungal β-N-acetylhexosaminidases are enzymes that are used in the chemoenzymatic synthesis of biologically interesting oligosaccharides. The enzyme from Aspergillus oryzae was produced and purified from its natural source and crystallized using the hanging-drop vapour-diffusion method. Diffraction data from two crystal forms (primitive monoclinic and primitive tetragonal) were collected to resolutions of 3.2 and 2.4 Å, respectively. Electrophoretic and quantitative N-terminal protein-sequencing analyses confirmed that the crystals are formed by a complete biologically active enzyme consisting of a glycosylated catalytic unit and a noncovalently attached propeptide.
Keywords: Catalytic Domain; Crystallography, X-Ray; Aspergillus oryzae; beta-N-acetylhexosaminidasy; krystalografie rentgenová; glykosylace; Crystallization; Glycosylation; katalytická doména; krystalizace; beta-N-Acetylhexosaminidases